The Lived Experience of the Faculty of Polytechnic University of the Philippines in the Implementation of Flexible Technology- Enhanced Learning (Flextel) - Pambuena, Elizabeth; Yango, Antonio R. (Technium Social Sciences Journal, 2023)
Nowadays, the use of technology in education is in demand due to the new normal set-up in our educational system. Connecting with students is one of the most rewarding aspects of a professor’s job. However, the FLEXTEL mode of learning creates a struggle because there is not enough time to design a truly flexible medium, difficult to prevent cheating, and its difficulties in access to ICT. Many colleges and universities have begun to offer online courses because of the rapid development of the Internet. Traditional face-to-face training is no longer a feasible option. However, there are numerous worries and issues developed, especially in terms of the quality of online education (Dhawan, 2020). This study aimed at determining the lived experience of faculty in the implementation of flexible technology-enhanced learning at PUP Branches and campuses in NCR. Generally, this study was designed with the following objectives: to understand the lived experience of the faculty in the implementation of Flexible Technology -Enhanced Learning and to describe how the faculty face the issues and challenges in the implementation of Flexible Technology-Enhanced Learning at the Polytechnic University of the Philippines, Branches and Campus-National Capital Region. The salient findings of the study are as to the lived experiences of faculty in the implementation of Flexible Technology Enhanced Learning our themes about the experiences of faculty emerged: Theme 1 focused on the exciting yet challenging experience of faculty in facing the reality of implementing FLEXTEL as prescribed by the University. It is about their acceptance in the beginning and their struggles along the way. Theme 2 was about the problems encountered in terms of disruptions and internet outages which emphasized its effect during the implementation. Theme 3 is a description of the faculty’s need for ample preparation which also signifies a of time on their part lastly, theme 4 centered on the burden of the faculty on the possible decrease of students’ performance as they employ FLEXTEL in their teaching and learning process. In general, themes supported the overall views of faculty’s experiences in the implementation of FLEXTEL. Then, as to how the faculty faced issues and challenges in the implementation of Flexible Technology Enhanced Learning there were three essential emerging themes explained: Theme 5: Flexibility and positivity at work highlighted the faculty’s attitude in response to the issues and challenges encountered; Theme 6: Continues learning and Upskilling stressed the importance of keeping themselves willing to learn new things and upgrade their skills to meet the demands of this system and lastly, Theme 7: Self-Reflective Change emphasized the necessity of change from within to easily adapt changes in terms of strategies and approaches. Undoubtedly, the participants acknowledged that though there are issues and challenges encountered in the implementation of FLEXTEL, there are still ways to manage it no matter how tough it is. Furthermore, based on the textural and structural descriptions, the following conclusions were drawn: the lived experiences of faculty in the implementation of Flexible Technology Enhanced Learning are indeed exciting yet challenging. It is sensational at first yet, during the process it is filled with struggles to defeat; and the faculty have acknowledged that student learning is the heart of every teaching process therefore, they need to face whatever issues and challenges are encountered in the implementation of FLEXTEL.